Impact of internal displacement on psychosocial and health status of students residing in the hostel of Anbar University, Iraq - Al-Samarrai, Mustafa Ali Mustafa; AL- Any, Ban Nadhum; Al-Delaimy, Ahmed K.; Yahyaa, Badeaa Thamer; Ali Jadoo, Saad Ahmed (Journal of Ideas in Health, 2020)
Background: Displacement in Iraq has been widespread and for frequent periods. Education was one of the most prominent victims of displacement at all levels, including higher education. This study aims to assess the impact of displacement on the psychosocial and health status of undergraduate students living in student accommodation of Anbar University, Iraq. Methods: A retrospective cross-sectional study was conducted from 3rd to 17th April 2017. Data was collected using a universal sampling technique. A total of 355 students (Response Rate: 82.1%.) completed a self-administered questionnaire consisting of 26 close-ended questions related to the socio-demographic and economic characteristics of students. Data were analyzed using SPSS version 16. Descriptive data presented as the mean and standard deviation (±SD). Results: The mean age (±SD) was 22.1 (±1.7) years (range 18-29). About two-third (240, 67.6%) of students experienced some mental disorders. Moreover, 25.1% of students confirmed that the mental disorders were negatively related to their level of performance in college, and the treatment was not available for 31.0% of them. Because of ID, about 45.4% of surveyed students had lost at least one academic year, and 17.5% began to smoke tobacco during the ID period. However, the social and psychological support was absent for about 57.4% of respondents. Conclusion: Our results suggest an urgent and strategic plane to improve the quality of logistics, health, and infrastructure of student accommodation.